(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Contextual architecture is a concept used in creating building design and functions with due consideration for local characteristics to ensure sustainability with the surrounding or pre-existing conditions. The Bandung Institute of Technology (ITB) campus is divided into three zones which are heritage or traditional, transition, and modern. A building is, however, located between the heritage and transition zones which are known as the Campus Center and considered to have damaged the zoning division on the master plan for the area due to the presence of new modern building designs. This study was, therefore, conducted to determine the common thread existing between the Campus Center and the surrounding two zones, the heritage zone with the West Hall case, and the transition zone with the engineering laboratory V case. Descriptive, analytic, and interpretative methods, with contextual theory, archetypes, ordering principles were used and the results showed the three buildings have a common thread which includes the roofs, columns, hallways, and corridors but only the Campus Center has columns, hallways, and corridors. The findings of this study are expected to provide theoretical and pragmatic benefits for writers and readers. Theoretically, the object dissection knowledge with archetypes and order elements to obtain the contextual forms of the building was provided while the pragmatic aspect focuses on understanding the contextual form of modern buildings.